Analisisi Kreativitas Peserta Didik dalam Mata Pelajaran SBdP Berbasis Kearifan Lokal di SD Negeri 2 Hadipolo - Putri, Meutia Revana Cahya; Marshelyna, Mela; Wijayanto, Wasis (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
This study aims to determine the level of student creativity, factors that influence student creativity, and how the application of local wisdom-based collage techniques affects student creativity in SBDP learning at SD N 2 Hadipolo Kudus. The method used in this study is a qualitative method with a case study approach. The object of this study is the focus of all grade 4 students of SD N 2 Hadipolo Kudus. In terms of classroom management, researchers formulate learning objectives so that students understand and appreciate batik art as a local culture through interactive strategies, where they decorate sketches with batik paper, thereby developing creativity and introducing regional cultural heritage. Student creativity in SBDP learning is influenced by gender, culture, and environmental factors. In a local context, such as at SD N 2 Hadipolo, student creativity is developed through a local wisdom-based approach, such as batik art, which not only improves creative skills but also fosters a sense of love and appreciation for regional culture.